Global prevalence of polypharmacy and potentially inappropriate medication in older patients with dementia: a systematic review and meta-analysis - Zhao, Mengnan; Chen, Zhaoyan; Xu, Ting; Fan, Ping; Tian, Fangyuan (Frontiers in Pharmacology, 2023)
Background Older patients with dementia always need to multiple drug due to comorbidities and cognitive impairment further complicate drug treatment, increasing the risk of potentially inappropriate medication. The objective of our study is to estimate global prevalence of polypharmacy and potentially inappropriate medication and explore factors of potentially inappropriate medication for older patients with dementia.We search PubMed, Embase (Ovid), Web of Science databases to identify eligible studies from inception to June 16 2023. We conducted a meta-analysis for observational studies reporting the prevalence of potentially inappropriate medication and polypharmacy in older patients with dementia using a random effect model. The factors associated with potentially inappropriate medication were meta-analyzed.Overall, 62 eligible studies were included, of which 53 studies reported the prevalence of potentially inappropriate medication and 28 studies reported the prevalence of polypharmacy. The pooled estimate of potentially inappropriate medication and polypharmacy was 43% (95%CI 38-48), 62% (95%CI 52-71), respectively. Sixteen studies referred factors associated with PIM use, 15 factors were further pooled. Polypharmacy (2.83, diabetes (1.31,, heart failure (1.17, 95%CI 1.00-1.37), depression (1.45, 95%CI 1.14-1.88), history of cancer (1.20, 95%CI 1.09-1.32), hypertension (1.46, 95%CI 1.05-2.03), ischemic heart disease (1.55, 95%CI 0.77-3.12), any cardiovascular disease (1.11, 95%CI 1.06-1.17), vascular dementia (1.09, 95%CI 1.03-1.16), chronic obstructive pulmonary disease (1.39, 95%CI 1.13-1.72) and psychosis (1.91, 95%CI 1.04-3.53) positively associated with potentially inappropriate medication use.prevalent in older patients with dementia. Among different regions, the pooled estimate of PIM use and polypharmacy varied widely. Increasing PIM in older patients with dementia was associated with polypharmacy closely. When suffered other comorbidity such as heart failure, diabetes prescribing should be cautioned.